Intestinal microsporidiosis: a hidden risk in rheumatic disease patients undergoing anti-tumor necrosis factor therapy combined with disease-modifying anti-rheumatic drugs? - Aikawa, Nadia Emi (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVE: Immunosuppressed patients are at risk of microsporidiosis, and this parasitosis has an increased rate of dissemination in this population. Our objective was to evaluate the presence of microsporidiosis and other intestinal parasites in rheumatic disease patients undergoing anti-tumor necrosis factor/disease-modifying anti-rheumatic drug treatment. METHODS: Ninety-eight patients (47 with rheumatoid arthritis, 31 with ankylosing spondylitis and 11 with psoriatic arthritis) and 92 healthy control patients were enrolled in the study. Three stool samples and cultures were collected from each subject. RESULTS: The frequency of microsporidia was significantly higher in rheumatic disease patients than in control subjects (36 vs. 4%, respectively; p<0.0001), as well as in those with rheumatic diseases (32 vs. 4%, respectively; p<0.0001), ankylosing spondylitis (45 vs. 4%, respectively; p<0.0001) and psoriatic arthritis (40 vs. 4%, respectively; p<0.0001), despite a similar social-economic class distribution in both the patient and control groups (p = 0.1153). Of note, concomitant fecal leukocytes were observed in the majority of the microsporidia-positive patients (79.5%). Approximately 80% of the patients had gastrointestinal symptoms, such as diarrhea (26%), abdominal pain (31%) and weight loss (5%), although the frequencies of these symptoms were comparable in patients with and without this infection (p>0.05). Rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis disease activity parameters were comparable in both groups (p>0.05). The duration of anti-tumor necrosis factor/disease-modifying anti-rheumatic drugs and glucocorticoid use were also similar in both groups. CONCLUSION: We have documented that microsporidiosis with intestinal mucosa disruption is frequent in patients undergoing concomitant anti-tumor necrosis factor/disease-modifying anti-rheumatic drug therapy. Impaired host defenses due to the combination of the underlying disease and the immunosuppressive therapy is the most likely explanation for this finding, and this increased susceptibility reinforces the need for the investigation of microsporidia and implementation of treatment strategies in this population.